Microbiological diagnosis of polymicrobial periprosthetic joint infection revealed superiority of investigated tissue samples compared to sonicate fluid generated from the implant surface. (May 2021) - Rieber, Heime; Frontzek, Andre; Heinrich, Stephanie; Breil-Wirth, Andreas; Messler, Julian; Hegermann, Stefan; Ulatowski, Martin; Koutras, Christos; Steinheisser, Enno; Kruppa, Thomas; Fischer, Martin; Hammer, Michael; et al.
Highlights: Periprosthetic joint infection (PJI) is a serious complication in implant failure. This study investigated 258 patients after revision arthroplasty. The results of tissue cultures were compared with those of sonicate fluid cultures. The results revealed superiority of tissue cultures in detecting polymicrobial PJI. The choice of culture media has a significant influence on the quality of results. Abstract: Objectives: In the microbiological diagnosis of periprosthetic joint infection (PJI), there is much discussion about the methodology of obtaining proper specimens, the processing technique, and suitable culture media. This retrospective study was conducted to analyse the accuracy of our culture techniques. Methods: Tissue samples and components from 258 patients after revision arthroplasty of the hip, knee, and shoulder were investigated, and the results of tissue cultures (TC) were compared to those of sonicate fluid cultures (SFC). Furthermore, an evaluation was performed of the influence of different culture media on the detection rate. Results: PJI was confirmed in 186 patients. The overall sensitivity of TC was no different to that of SFC (91.3% vs 90.8%, P = 1). In 153 cases (82.3%), TC and SFC showed concordant positive results. Results were discordant in 33 cases (17.7%). When differentiated according to the type of infection, TC showed significantly better results than SFC in detecting polymicrobial infections (97.0% vs 67.0%, P = 0.004). There were also significant differences between the culture media regarding the yield of microorganisms. Conclusions: TC was more effective in detecting co-infections. The best results were obtained using both TC and SFC. The choice of culture media has a significant influence on the quality of results.